Pengaruh Penerapan Anggaran Berbasis Kinerja Terhadap Akuntabilitas Kinerja Pada Seluruh OPD Kabupaten Pamekasan - Attamimi, Dafiq Fikri; Lestari, Yona Octiani (Akuisisi : Jurnal Akuntansi, 2023)
The purpose of this study was to determine the effect of the implementation of performance-based budgeting on performance accountability in all OPD Pamekasan Regencies. The implementation of this performance-based budget uses four variables, namely, budget planning (X1), budget execution (X2), budget accountability (X3), and performance evaluation (X4). The study used primary data from a questionnaire distributed to several employees concerned as many as 139 respondents from all OPD as 38 OPD in Pamekasan Regency. This research uses multiple linear regression analysis methods. The results showed that budget execution and performance evaluation had an effect on performance accountability, while budget planning and budget accountability had no significant effect on performance accountability. The conclusion from the results of this study is that budget implementation and performance evaluation have a positive effect, while budget planning and budget accountability have a negative effect on the performance accountability of government agencies.